Whole exome sequencing reveals a novel de novo FOXC1 mutation in a patient with unrecognized Axenfeld-Rieger syndrome and glaucoma - Pasutto, F.; Mauri, L.; Popp, Bernt; Sticht, Heinrich; Ekici, Arif Bülent; Piozzi, E.; Bonfante, A.; Penco, Silvana; Schlötzer-Schrehardt, Ursula; Reis, André (Gene, 2015)
We report the identification of a novel mutation in the fork-head box C1 (FOXC1) gene which occurred de novo in an Italian patient with unrecognized Axenfeld-Rieger syndrome. He was previously diagnosed as having late recognized primary congenital glaucoma at the age of 14 years and was subsequently subjected to multiple surgical interventions due to uncontrolled intraocular pressure and progressive visual field loss. After exclusion of mutations in CYP1B1 and MYOC, trio-whole-exome sequencing revealed de novo in frame deletion in the coding region of the FOXC1 gene (c.407_409delGTC, p.V137del) leading to a deletion of the evolutionary conserved amino acid Valine at position 137 of the protein. Molecular modeling predicted that Val137 deletion impairs FOXC1 DNA-binding capacity and transcriptional activation. Since loss-of-function mutations in FOXC1 are associated with Axenfeld-Rieger syndrome, the genetic findings in combination with re-evaluation of the patient's clinical data resulted in a corrected diagnosis of Axenfeld-Rieger syndrome with developmental glaucoma. We therefore suggest that in addition to CYP1B1 and MYOC, FOXC1 should be included in the genetic analysis of cases with unclear glaucomatous phenotypes to ensure proper diagnosis, adequate treatment and appropriate genetic counseling.
EVALuna2:9257